Tuning of Power System Stabilizers Using Multiobjective Optimization Nsga Ii - Becker-Cares, C; Verdejo-Fredes, H; Gonzalez-Moraga, D (IEEE Computer Society, 2015)
This article presents the application of the NSGA II genetic algorithm to the tuning parameters of the power system stabilizer. In order to obtain the adjustment needed, three objective functions were proposed to be minimized. Which depend directly on the localization of the real part of eigenvalues of the system under study. By using the search algorithm, a set of feasible solutions are obtained, and then the best is selected according to the parameter combination which satisfy the rigorous criteria related to the dynamic answer of the system. The methodology is applied to two international tests: three machines - nine bus and ten machines-thirty nine bus. © 2015 IEEE.